International dimensions of the China Dream: A case study of media coverage in Kenya - Lee, Charlotte (Universitas Negeri Yogyakarta, 2024)
This paper examines media coverage of China-sponsored development projects in Kenya in order to understand more deeply China's global soft power strategies. Kenya is a hub for China's media presence on the African continent and also an important node in China's Belt and Road Initiative. Examination of Kenyan news content in the period immediately following the 2012 launch of Xi Jinping's signature concept, the China Dream, as well as regression analysis of newspaper article characteristics, finds that the China Dream concept has not been adopted in a meaningful way by host country media outlets. This highlights the challenges facing China's leaders in shaping public narratives within countries characterized by strong independent media traditions.